Potential Indonesian Medicinal Plants on Aphrodisiac Activity - Prasetya, Fajar; Bahar, Zulhaerana; Fricillia, Onny Ziasti; Indriyanti, Niken (Indonesian Journal of Pharmaceutical Science and Technology, 2024)
The use of Indonesian medicinal plants in empirical ingredients as a jamu in Indonesian tradition is very interesting to be explored. One of them is the use of jamu for aphrodisiac activity. This research is aimed to determine the data about the diversity of Indonesian medicinal plants used for aphrodisiacs. Some aspects reviewed were empirical use, safety data, and scientific research data. The method used in this research is narrative review by using search engine Sciencedirect, Pubmed, Springerlink, and Google Scholar in 24 years (2000-2024). The literature review resulted in 20 Indonesian medicinal plants, which were very potent for aphrodisiac. The plants are Areca catechu L., Pimpinella panatjan Mirb, Zingiber officinale, Dendrocalamus asper, Eurycoma longifolia Jack, Sanrego, Anacardium occidentale L., Imperata cylindrica L., Allium sativum L., Ocimum sanctum, Piper retrofractum Vahl., Piper nigrum L., Eugenia caryophyllata, Myristica Fragans, dan mangrove mangrove M. muticus, R. mucronata, R. apiculata, A. aureum, D. trifoliata and B. parviflora. Therefore, it will be used as a reference based for the further research.